Snoring is associated with hypertension and diabetes mellitus among adults in north Sudan: a cross-sectional study - Amal O. Bashir; Mousab A. Elimam; Mohamed A. Elimam; Ishag Adam (BMC, 2024)
Abstract Background Different levels of association between snoring, hypertension, and diabetes mellitus (DM) are reported. There are few published studies on this topic in African countries, and no investigation was conducted in Sudan. This study aimed to assess the prevalence and factors associated with snoring and the association between snoring, hypertension, and type 2 DM (T2DM) in northern Sudan. Methods A community-based cross-sectional study using a multistage sampling technique was conducted in four villages in the River Nile state of northern Sudan from July to September 2021. Sociodemographic characteristics were collected using a questionnaire. Body mass index (BMI) was measured using standard methods, and a multivariate analysis was conducted using the Statistical Package for the Social Sciences® (SPSS®) for Windows, version 22.0. Results Of the 384 adults, 193 (50.3%) were males and 191 (49.7%) were females. Of the adults, 38 (9.9%) were underweight, 121 (31.5%) had average weight, 113 (29.4%) were overweight, and 112 (29.2%) were obese. One hundred and six (27.6%) adults were snorers. Multivariate analysis showed that increasing age (adjusted odds ratio [AOR] = 1.02, 95% confidence interval [CI] = 1.01‒1.04), increasing BMI (AOR = 1.04, 95 CI = 1.01‒1.08), obesity (AOR = 2.0, 95% CI = 1.10‒3.69), and alcohol consumption (AOR = 2.32, 95% CI = 1.14‒4.74) were positively associated with snoring. Of the 384 adults, 215 (56.0%) had hypertension. Multivariate analysis showed that increasing age (AOR = 1.04, 95% CI = 1.02‒1.06), increasing BMI (AOR = 1.08, 95% CI = 1.04‒1.13), female sex (AOR = 1.7, 95% CI = 1.08‒2.73), and snoring (AOR = 1.69, 95% CI = 1.02‒2.82) were positively associated with hypertension. One hundred and six (27.6%) adults had T2DM. Multivariate analysis showed that increasing age (AOR = 1.03, 95% CI = 1.01‒1.05) and snoring (AOR = 1.78, 95% CI = 1.09‒2.91) were associated with T2DM. Conclusion Around one-fourth of the adults in Northern Sudan are snorers. Snoring is more common among obese adults. Snoring is associated with increased odds of hypertension and T2DM. Adults who snore must pay close attention to their blood pressure and blood glucose levels to prevent hypertension and DM.